2006
DOI: 10.1590/s1516-31802006000500012
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on clinical management of antipsychotic-induced sexual dysfunction in schizophrenia

Abstract: INTRODUCTION: Sexual dysfunction frequently occurs in patients with schizophrenia under antipsychotic therapy, and the presence of sexual side effects may affect compliance. The aim of this study was to review and describe clinical findings relating to the appropriate management of such dysfunctions. MATERIAL AND METHODS: The research was carried out through Medline (from 1966 to March 2005), PsycInfo (from 1974 to March 2005), and Cochrane Library (from 1965 to March 2005) and included any kind of study, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 57 publications
1
25
0
1
Order By: Relevance
“…7 The formula called Peony-Glycyrrhiza Decoction (PGD) made from Paeoniae and Glycyrrhiza radices (Shaoyao-Gancao-Tang in Chinese and Shakuyaku-Kanzo-To in Japanese, TJ-68) is such agent that has been introduced into the treatment of various conditions associated with hyperprolactinemia by medical professionals in China and Japan. [8][9][10][11][12][13] Peony-Glycyrrhiza Decoction was originally recorded in the ancient Chinese pharmacopoeia called Treatise on Exogenous Febrile Diseases (written by Zhang ZhongJing, 200-400 B.C.) and used for alleviating muscle spasm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 The formula called Peony-Glycyrrhiza Decoction (PGD) made from Paeoniae and Glycyrrhiza radices (Shaoyao-Gancao-Tang in Chinese and Shakuyaku-Kanzo-To in Japanese, TJ-68) is such agent that has been introduced into the treatment of various conditions associated with hyperprolactinemia by medical professionals in China and Japan. [8][9][10][11][12][13] Peony-Glycyrrhiza Decoction was originally recorded in the ancient Chinese pharmacopoeia called Treatise on Exogenous Febrile Diseases (written by Zhang ZhongJing, 200-400 B.C.) and used for alleviating muscle spasm.…”
mentioning
confidence: 99%
“…Today, numerous studies have confirmed the antispasmodic effects of this herbal formula and its major constituents on various spasmodic conditions. 14-16 Furthermore, a large number of studies have shown that PGD is also effective in treating disorders associated with sexual and reproductive hormone dysfunctions, including infertility, 17 ovulation disorders, 18,19 menopause, 20 hyperprolactinemia-induced impotence, 13 and neuroleptic-induced hyperprolactinemia in schizophrenic individuals, [8][9][10][11] as evidenced by a significant suppression of elevated PRL levels and resumption of sexual desire and menstrual cycle, without incidence of severe adverse events. [8][9][10][11] Animal studies further demonstrated that PGD and its major constituents possess a capacity of modulating synthesis and release of several sexual and reproductive hormones, including PRL.…”
mentioning
confidence: 99%
“…There was a lack of randomized controlled trials on the clinical management of antipsychoticinduced sexual dysfunction in the literature, and no proper comparisons of the efficacy of agents (Costa, Lima, & Mari, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the childhood and adolescence specialty, for example, EBP ranged from anxiety disorder, whether for treatment (18) or assessment (19) , vaccination (24)(25) , safety during nebulization (28) , ICU death (29) , physical exercise measure (33) , nutritional interventions and child growth (70) , prenatal and weight at birth (71) , among others. Another quite diversified example comes from psychiatry/mental health: medication treatments (15,18,20,76,80,89) , physical exercise (16) , cognitive therapy (17) , anxiety assessment instrument (19) , quality of life and food disorders (35) , psychological stress x hypertension (40) , family intervention in schizophrenia (50) etc.…”
Section: Discussionmentioning
confidence: 99%